AN ANALYSIS TRANSLATION OF FIGURE OF SPEECH IN THE NOVEL “TO ALL THE BOYS I’VE LOVED BEFORE” - Miftah Kevin Iswara; Evert Haryanto Hilman (IdeBahasa, 2022)
This research is entitled an analysis of figurative language in novel "To All The Boys I've Loved Before" by Jenny Han. The research aims to explain the translation method by Newmark (1988) used in translating simile, hyperbole, antonomasia, metaphor, and association and also to find out the types of figurative language. This research applies the descriptive qualitative method. The researcher focuses on 5 kinds of figurative language and has found 26 similes, 19 hyperboles, 2 antonomasias, 2 metaphors, and 1 association in the novel. From 6 out of 50 data, there are five translation methods applied in the translation consisting of literal translation (84%), word-for-word (6%), semantic translation (2%), idiomatic translation (2%), and adaptation (6%).